Social Well-being of the Megalopolis Population as an Integral Indicator - P. P. Deriugin; L. A. Lebedintseva; O. V. Yarmak; Shi Yi; E. A. Kamyshina (Дискурс)
Introduction. The basic theoretical and methodological approaches to the study of the social well-being of the population of megacities as an integral indicator, as well as current trends in the development of new diagnostic methods are considered. The experience of empirical sociological research is presented, showing methodological algorithms for system fixation and processing of the main indicators-indicators.Methodology and sources. The analysis of the theoretical and methodological foundations for diagnosing the social well-being of residents of a metropolis as an integral indicator is carried out on the basis of a set of scientific approaches. They combine the characteristics of objective and subjective indicators in a single research procedure that ensure the integrity of the external and internal characteristics of the object of study.Results and discussion. From the methodological point of view, the diagnosis of social well-being is built as a system analysis of three groups of data. Firstly, the protection of residents of St. Petersburg from social dangers and threats can be measured on the basis of indicators such as environmental threats; harassment due to gender and age; arbitrariness of officials; infringement due to nationality and religious beliefs; arbitrariness of officials; political persecution; poverty; loneliness; crime. Secondly, satisfaction with life is diagnosed by referring to such parameters as attitude to the region of residence; satisfaction with life in general. Thirdly, the degree of social optimism is revealed on the basis of appeal to such parameters as confidence in the future; comparison of the present and past lifestyle; future life forecast.Conclusion. This paper captures an important point in methodological and methodological unity in approaches. In the research methodology, the integral nature of social well-being involves an appeal to theoretical and conceptual principles that are aimed at exploring such unity. Further, the same trend is continued in integrated methods for the integrated diagnosis of social well-being.